Whose Record Is It Anyway? Putting Patients' Interests at the Heart of the Implementation and Use of Electronic Medical Records - Rebecca L. Mador, Nicola T. Shaw, Stephen Cheetham and Robert J. Reid (ElectronicHealthcare, 2008)
With the dawn of electronic medical records (EMRs) and patient portals, there is an unprecedented opportunity to provide truly collaborative patient-centred care. These tools can promote communication between healthcare providers and patients, improve chronic disease management and enable patients to become active members in the healthcare delivery system, but only if the tools work for everyone involved - including patients. Without patient consultation and input, there will be limitations in the ways in which physicians and patients are able to capitalize on these tools. Decision-makers must begin to enact their commitment to collaborative patient-centred care by engaging patients in discussions related to EMR design, implementation and use.
Keywords: Electronic Medical Record, EMR, Patient-Centered Care, Canada, Patient Participation